Infections in 100 Cord Blood Transplantations - Amar Safdar; Gilhen Rodriguez; Marcos J. de Lima; Demetrios Petropoulos; Roy F. Chemaly; Laura L. Worth; Elizabeth J. Shpall; Kenneth V. I. Rolston; Issam Raad; Ka Wah Chan; Richard E. Champlin (2007)
Cord blood-derived stem cells are successfully used in the treatment of cancer and congenital disorders in children. This alternative source of stem cells is also explored for adult cancer patients with limited donor options. However, delayed engraftment, prolonged neutropenia, secondary graft loss, and graft-versus-host disease (GVHD) in recipients of cord blood transplantation (CBT) make opportunistic infections a serious concern. We evaluated the spectrum of infections in adults and children undergoing CBT at our National Cancer Institute-designated comprehensive cancer center. The infection incidence rate ratio (total infection episodes/days at risk [survival after CBT] × 100) was 2.4 times higher in 35 adult patients than in 62 children, especially in adults with neutropenia (3 × higher) and GVHD (1.9 × higher). Ninety-two percent of fungal infection episodes occurred within 100 days after transplantation; half of these infections occurred in the first 30 days after CBT. Most bacterial infections (80%) were also diagnosed in the first 100 days, whereas late (>100 d) post-CBT cytomegalovirus and varicella zoster virus infections occurred only in children with chronic GVHD. Multivariate analysis showed that resolution of lymphocytopenia (≥1000 cells/μL) (hazard ratio [HR] 0.71; p < 0.0001) and successful engraftment (HR 0.20; p < 0.0001) were associated with a low risk of serious infection. Children (HR 0.36; p < 0.0002) with sustained engraftment (HR 0.39; p < 0.004) and those with cancer in remission (HR 0.47; p < 0.007) were less likely to die from infection. More effective measures for surveillance and prevention of late cytomegalovirus and varicella zoster virus infections in children with CBT and chronic GVHD are needed. Abbreviations: BCG = bacilli Calmette-Guèrin, CBT = cord blood transplantation, CMV = cytomegalovirus, GVHD = graft-versus-host disease, HHV = human herpesvirus, HLA = human lymphocyte antigen, HR = hazard ratio, VZV = varicella zoster virus.